2021
DOI: 10.1186/s12877-021-02158-1
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic role of functional dependency in older inpatients with COVID-19

Abstract: Background Coronavirus disease 2019 (COVID-19) is a pandemic infection with substantial risk of death, especially in elderly persons. Information about the prognostic significance of functional status in older patients with COVID-19 is scarce. Methods Demographic, clinical, laboratory and short-term mortality data were collected of 186 consecutive patients aged ≥ 65 years hospitalized with COVID-19. The data were compared between 4 study groups: (1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 19 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…In line with our results, a previous study found that disability was addictive to age ≥ 80 years in characterizing prognosis of older seniors hospitalized for SARS-CoV-2 infection. In particular, the group with older age and functional dependency showed a mortality risk 10 times higher than their counterparts [ 24 ]. In another experience involving ≥ 75 years patients, pre-infection disability and frailty significantly improved the accuracy of prognostic models, when added to clinical variables commonly used for younger individuals [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In line with our results, a previous study found that disability was addictive to age ≥ 80 years in characterizing prognosis of older seniors hospitalized for SARS-CoV-2 infection. In particular, the group with older age and functional dependency showed a mortality risk 10 times higher than their counterparts [ 24 ]. In another experience involving ≥ 75 years patients, pre-infection disability and frailty significantly improved the accuracy of prognostic models, when added to clinical variables commonly used for younger individuals [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Symptoms of coronavirus disease 2019 (COVID- 19) in patients are reported to vary from minor symptoms (such as headache, fatigue, and fever) to severe symptoms (such as dyspnea or hypoxia) (1)(2)(3)(4). With this wide range of clinical characteristics and disease outcomes, differences between nonelderly and old patients have also been reported (1,(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“… 41 Due to the reduction of nutritional intake caused by a decreased appetite and the increase in nutritional consumption caused by systemic inflammation, the nutritional statuses of elderly females are worse than those of young and middle-aged females. 16 , 43 We show that elderly females have the highest inflammatory load and the lowest nutritional status. Indicators of inflammatory and nutritional status were the most appropriate prognostic factors for elderly female patients.…”
Section: Discussionmentioning
confidence: 76%